Differences of type of foods consumed by households in urban and rural West Java, Indonesia - Annisa Nurhidayati Vieta; Riyadi Hadi (BIO Web of Conferences)
Dietary diversity is a critical indicator of food and nutrition security, with a minimum consumption of four food groups shown to lower the risk of malnutrition and related health issues. This study aims to assess household dietary diversity scores and examine differences in food consumption patterns between urban and rural households in West Java. The study involved 300 households in Sukabumi City and Cianjur District in June 2022. While urban households have a higher prevalence of dietary diversity (78%) compared to rural areas (68%), these differences are not statistically significant. Food insecurity and stunting remain high across both settings, with rural households experiencing higher rates of both. The study also notes that while higher dietary diversity includes diverse food groups in both urban and rural areas, disparities in access remain, especially in rural areas where diets are more limited. Households in low and medium dietary diversity only consumed eggs as primary protein sources. Programs promoting diverse protein source consumption could help reduce the incidence of food insecurity and stunting, especially in rural settings.